Anxiety among Higher Secondary Students: A Factorial Study of Gender and Locality DifferencesAnxiety among Higher Secondary Students: A Factorial Study of Gender and Locality Differences (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Adolescent anxiety is increasingly recognized as a significant psychological concern affecting academic functioning and emotional well-being. The present study examined anxiety levels among higher secondary students and investigated whether gender and locality differences exist using a 2×2 factorial design. The sample consisted of 40 students (10 boys and 10 girls from urban schools; 10 boys and 10 girls from rural schools) selected through random sampling from Jammu district. Anxiety was assessed using a standardized self-report inventory. Data were analyzed using two-way Analysis of Variance (ANOVA). Results revealed no statistically significant main effects of gender (F = 0.021, p > .05) or locality (F = 0.91, p > .05), and no significant interaction effect between gender and locality (F = 1.92, p > .05). Findings suggest that adolescent anxiety in this sample appears to be a generalized developmental phenomenon rather than one determined by demographic factors. Implications for universal school-based mental health interventions are discussed.